2012
DOI: 10.1002/mnfr.201100640
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin FB1 treatment acts synergistically with methyl donor deficiency during rat pregnancy to produce alterations of H3‐ and H4‐histone methylation patterns in fetuses

Abstract: Scope Prenatal folate and methyl donor malnutrition lead to epigenetic alterations that could enhance susceptibility to disease. Methyl‐deficient diet (MDD) and fumonisin FB1 are risk factors for neural tube defects and cancers. Evidence indicates that FB1 impairs folate metabolism. Methods and results Folate receptors and four heterochromatin markers were investigated in rat fetuses liver derived from dams exposed to MDD and/or FB1 administered at a dose twice higher than the provisional maximum tolerable dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 52 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…This is the first study that investigates the gene-specific DNA methylation in the toxicity mechanisms of FB1 for the risk assessment process. In a recent study on the epigenetic mechanisms in FB1 toxicity, FB1 can alter histone modifications which lead to heterochromation disorganization at low doses (Pellanda et al, 2012). In this work, it was shown that H4K20me3 significantly decreased, while H3K9me3 significantly increased in the fetuses when pregnant dams were exposed to methyl-deficient diet and FB1 (Pellenda et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…This is the first study that investigates the gene-specific DNA methylation in the toxicity mechanisms of FB1 for the risk assessment process. In a recent study on the epigenetic mechanisms in FB1 toxicity, FB1 can alter histone modifications which lead to heterochromation disorganization at low doses (Pellanda et al, 2012). In this work, it was shown that H4K20me3 significantly decreased, while H3K9me3 significantly increased in the fetuses when pregnant dams were exposed to methyl-deficient diet and FB1 (Pellenda et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…FB 1 can also induce epigenetic changes through the post-translational modifications of histones, but no study to date has investigated these changes in humans [ 63 , 64 , 65 ]. Here, we identified changes to H3K4 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mechanisms of fumonisin carcinogenicity do not appear to involve interaction with DNA and the carcinogenic activity of fumonisins may be mediated via epigenetic mechanisms (Coulombe 1993). Fumonisin B1 induced hypermethylation of DNA (Mobio et al 2000) and may be involved in histone modifications (Pellanda et al 2012). Ochratoxin A also has epigenetic effects (Marin-Kuan et al 2008) and is likely to act through a network of interacting epigenetic mechanisms, including protein synthesis inhibition, oxidative stress, and the activation of specific cell signaling pathways, which are responsible for carcinogenicity.…”
Section: Egigenetic Alterationsmentioning
confidence: 98%